JAGB 2.0: Improved Constraints on the J-region Asymptotic Giant Branch–based Hubble Constant from an Expanded Sample of JWST Observations - Siyang Li; Adam G. Riess; Daniel Scolnic; Stefano Casertano; Gagandeep S. Anand (The Astrophysical Journal, 2025)
The J-region asymptotic giant branch (JAGB) is an overdensity of stars in the near-infrared, attributed to carbon-rich AGB stars, and recently used as a standard candle for measuring extragalactic distances and the Hubble constant. Using JWST in Cycle 2, we extend JAGB measurements to six hosts of nine Type Ia supernovae (SNe Ia; NGC 2525, NGC 3147, NGC 3370, NGC 3447, NGC 5468, and NGC 5861), with two at D  ∼ 40 Mpc, all calibrated by the maser host NGC 4258. We investigate the effects of incompleteness and are unable to recover a JAGB measurement for NGC 3147. We compile all JWST JAGB observations of SN Ia hosts, 15 galaxies hosting 18 SNe Ia, from the SH0ES and CCHP programs, and employ all literature measures. We find no significant mean difference between these distances and those from Hubble Space Telescope Cepheids, −0.03 ± 0.02 (stat.) ± 0.05 (sys.) mag. We find a difference of 0.11 ± 0.022 mag between JAGB mode measurements in the CCHP analyses of two fields in NGC 4258, a feature also seen in two SH0ES fields (see field-to-field variations in S. Li et al.), indicating significant variation of NGC 4258 JAGB measurements, which produce a large absolute calibration uncertainty. Variations are also seen in the shape of the JAGB luminosity function (LF) across galaxies so that different measures produce different values of the Hubble constant. We look for but do not (yet) find a standardizing relation between JAGB LF skew or color dependence and the apparent variation. Using the middle result of all JAGB measures to calibrate SNe Ia yields a Hubble constant of H _0 = 73.3 ± 1.4 (stat.) ± 2.0 (sys.) km s ^−1 Mpc ^−1 with the systematic dominated by apparent differences across the NGC 4258 calibrating fields or their measures.